2021
DOI: 10.1021/acs.jpclett.1c03771
|View full text |Cite
|
Sign up to set email alerts
|

Is a Single Molecule Sufficient to Determine the Internal Charge Trapping Energy in Crystalline Organic Semiconductors?

Abstract: In silico diagnoses of charge-transfer efficiencies in organic semiconductors require the accurate computations of transport parameters. We show here that ignoring the molecular packing effects when computing the internal charge trapping energy may cause a severe deviation to the result deduced from the periodic crystal structure. This deviation can reach up to 100 meV in common organic materials. According to the semiclassical Marcus theory, this energy difference can lead to orders of magnitude change in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…22 We have previously shown that the above single-molecule approximation is valid only when the molecule-packing impacts are negligible. 23 In addition to molecular packing, another environmental factor that is often overlooked is the external electric field (EEF). 24 In a typical field-effect transistor, the EEF can be generated by the electrodes, and the gate voltage controls the channel conductivity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…22 We have previously shown that the above single-molecule approximation is valid only when the molecule-packing impacts are negligible. 23 In addition to molecular packing, another environmental factor that is often overlooked is the external electric field (EEF). 24 In a typical field-effect transistor, the EEF can be generated by the electrodes, and the gate voltage controls the channel conductivity.…”
mentioning
confidence: 99%
“…So far, λ is mostly calculated based on the isolated molecule via either the normal-mode analysis , or the Nelsen’s four-point method . We have previously shown that the above single-molecule approximation is valid only when the molecule-packing impacts are negligible . In addition to molecular packing, another environmental factor that is often overlooked is the external electric field (EEF) .…”
mentioning
confidence: 99%
See 1 more Smart Citation